2019
DOI: 10.1159/000501968
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of the Preferred Walking Speed in Individuals with Obesity

Abstract: <b><i>Background:</i></b> The preferred walking speed (PWS), also known as the “spontaneous” or “self-selected” walking speed, is the speed normally used during daily living activities and may represent an appropriate exercise intensity for weight reduction programs aiming to enhance a more negative energy balance. <b><i>Objectives:</i></b> The aim of this study was to examine, simultaneously, the energetics, mechanics, and perceived exertion determinants of PWS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In the present study, obese participants showed lower MWS compared to all other BMI categories in the present study (Figure 1). This finding supports previous studies (Fernández Menéndez et al, 2019; Liu & Yang, 2017), indicating that obese adults prefer to walk slower possibly in an effort to decrease the energy expenditure and increase comfort. The slower walking speed found in obese individuals is expected to reduce the energy expenditure, joint loads (DeVita & Hortobágyi, 2003), mechanical work (Malatesta et al, 2009), and/or ground reaction forces (Browning & Kram, 2007) resulting from the additional mass carried against gravity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, obese participants showed lower MWS compared to all other BMI categories in the present study (Figure 1). This finding supports previous studies (Fernández Menéndez et al, 2019; Liu & Yang, 2017), indicating that obese adults prefer to walk slower possibly in an effort to decrease the energy expenditure and increase comfort. The slower walking speed found in obese individuals is expected to reduce the energy expenditure, joint loads (DeVita & Hortobágyi, 2003), mechanical work (Malatesta et al, 2009), and/or ground reaction forces (Browning & Kram, 2007) resulting from the additional mass carried against gravity.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, as well as the environment affecting PA levels, it may also affect WS (Levine & Norenzayan, 1999). Although PWS and MWS have previously been related to factors such as maximal strength of lower extremities (Bohannon, 1997) or obesity (Fernández Menéndez et al, 2019), it is unclear how components of PA influence WS outcome measures in healthy young adults. Despite this, only three studies have examined walking behaviors in the Gulf and Arab regions, and all of them were limited due to small sample sizes [i.e., 15 females and 15 males from Kuwait (Al-Obaidi et al, 2003); 17 males from Tunisia (Dhahbi et al, 2014); nine males and nine females from Qatar (Majed et al, 2020)].…”
Section: Introductionmentioning
confidence: 99%
“…Common between UGS and MGS models were BMI and number of medications, in the clinically expected directions, i.e., obesity and number of medications had a negative impact on gait speed. As regards obesity, research has suggested that obese adults may select their walking speed to minimize pendular energy transduction, energy cost, and perceived exertion during walking (Fernández-Menéndez et al, 2019). In our UGS and MGS models, a BMI ≥29 kg/m 2 had negative impact association.…”
Section: Common Featuresmentioning
confidence: 70%
“…obesity and number of medications had a negative impact on gait speed. As regards obesity, research has suggested that obese adults may select their walking speed to minimize pendular energy transduction, energy cost, and perceived exertion during walking (56). In our UGS and MGS models, a BMI ≥29 kg/m 2 had negative impact association.…”
Section: Common Featuresmentioning
confidence: 70%